Eficiência energética de uma unidade de microgeração de energia elétrica a partir do biogás da suinocultura - Silva, Felipe Pinheiro (2015)
The swine farming is an important Brazilian agricultural business. The activity held in confinement generates a large volume of wastewater that may be treated by anaerobic digestion. To use the biogas generated in the process, it is necessary better knowledge through the variables involved. The objective of this study was the evaluation of biogas production parameters, power generation, generator set performance in biogas conversion into electricity and the avoided cost of electricity from of the farm. Biogas parameters were monitored as methane content, digester production, and the engine consumption in generation of electricity. Monitoring was realized with the use of instruments and storage of information in a database. The results indicated an average daily production of 443 m3.dia-1, with an average of 0.10 m3 of biogas per pig and 68% of methane content. The average electricity generation was 324,5 kWh.dia-1, and efficiency of the generator set was 17% with a power of 70 kW and an average of 6,5 hours of daily operation. The avoided cost by self-consumption of electricity generated was R$ 13,718.20, and during the monitoring 70.5 MWh of electricity was generated, of which 26.6 MWh were exported to the distribution network.